Alyssa Montoya: capstone - Montoya, Alyssa, artist (Colorado State University. Libraries, 2013)
The artist's statement: The goal of all of my pieces is to give it a short of cartoon like feature to it. I want to keep it fun and entertaining for the people who look at it. My goal is to get people involved and interested in my work. I don't want to be taken to seriously because I feel like it is better to be excited about something and have fun with it rather then be taken to seriously and not enjoy watching other people look at your pieces.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.